Bridging the gap between Networked Learning and Learning Analytics - Kilinska, Daria; Ryberg, Thomas; Kobbelgaard, Frederik Victor (Proceedings of the International Conference on Networked Learning, 2018)
Learning Analytics is a field that is constantly evolving, encompassing new perspectives and expanding into other research fields. This workshop was inspired by the 2012 call for action from Rebecca Ferguson in which she called for building stronger connections to the learning sciences (Ferguson, 2012). Although this call has not remained unanswered, we still find this connection to be insufficient to foster the development of technological solutions needed in the future. This is where the Networked Learning community comes into play. During this workshop, we wish to discover, reflect on and build connections joining the two fields, in the hope that a better understanding of what Networked Learning can offer the Learning Analytics community and vice versa will foster beneficial and productive collaborations in the future.